Relevansi Makna Empat Drama Anak-Anak Berbasis Cerita Dongeng Nusantara Bagi Generasi Masa Kini - Nur Sahid; Junaedi - (Mudra Jurnal Seni Budaya, 2022)
The era of digitalization is an era that is able to indicate a change in the dynamics of scientific and technological progress that must be responded positively by us to make the best use of it in various daily activities, including in "teaching and learning" educational activities. The purpose of this study was to determine how far the influence of the Edmodo mobile application to improve student learning outcomes in educational dance lectures through a blended learning approach that combines two learning strategies, namely conventional learning and virtual learning through the Edmodo mobile application system. This experimental study used a research sample of 36 students in semester 5 who contracted educational dance courses. To reveal more in-depth data and information in this study, researchers used quantitative data with data collection techniques usingobservation, interviews, and literature studies. Data analysis was carried out quantitatively with the SPSS 17.0 program. The results of the study show that (Mobile-Application) Edomodo is an application that can be accessed via smartphones or other technological devices such as laptops and computers, which can be used as forums or teaching and learning facilities in educational dance lectures by lecturers and students. The edomodo mobile application is able to create a learning space that can not only bedone in conventional learning, but can be done virtually unlimited learning with classroom lectures which are usually carried out in the classroom simultaneously and face to face.